Communicating risk to tourists: A mental models approach to identifying gaps and misperceptions. (January 2020) - Aliperti, Giuseppe; Nagai, Hayato; Cruz, Ana Maria
Abstract: This study compares the perspectives of government agencies, academic experts, and tourism suppliers on providing tourists with tsunami risk information. Previous studies highlight that government agencies are often in charge of developing tourism-oriented risk communication plans; academic experts are recognized as having a more in-depth understanding of the technical aspects of a risk, as well as the hazard development and potential effects; and tourism suppliers play a fundamental role during the risk communication process, due to direct connection with the tourists. However, tourists are often found to be insufficiently informed about risks and warning systems. We use the Mental Models approach, aiming to analyze the communication between the aforementioned categories of stakeholders. We carried out interviews and conducted field trips in Japan between April and December of 2018. Results highlight an increased general awareness regarding tourists' preparedness, poorly supported by risk-communication gaps, misperceptions, and a lack of efficacy analyses. Highlights: Risk communication: Informing tourists to increase their disaster preparedness during the emergency phase; Perspectives of governmental organizations, academic experts, and tourism suppliers; A mental models approach to evaluate, compare, and identify communication gaps and misperceptions; Barriers and opportunities to improve risk communication to tourists.